Diagnosa Kerapuhan Kelembagaan Perekonomian Pedesaan - Tri Pranadji (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2003)
EnglishInstitutional brittleness could be considered as the major cause of rural economy development failure, and ultimately it is reflected in national economy that have been hit economic crisis. In addition, the economic, financial and industrial designers have less understanding on how important agricultural sector in supporting national economy (agricultural development policy makers tend to follow them), and they also possess less knowledge of how important institutional roles in rural economy development. If only at the initial stage, the rural economic institutional had been firmly established and then established an agricultural endowment richness based national economy development, then not only rural communities will be free of the tempestuous economic crisis (as still takes place up to date) but also the national economy will describe the greatness of rural community’s economy transformation with a good sample of social system for many countries. Rural economy institutional fragility is indicated by ineffective leader factor empowerment (as a progress mover) in rural areas, let values and norms leading for rural economic progress undeveloped, rural economic organization and structure had been let to be flimsy, autonomy aspect had not lifted rural community’s political power in economic activities and ignored rural human resource competence factors.IndonesianKerapuhan kelembagaan bisa dipandang sebagai “biang keladi” kegagalan pengembangan perekonomian pedesaan, yang pada gilirannya hal ini tercermin pada perekonomian nasional yang tidak dapat mengelak dari krisis. Selain para perancang pembangunan di kalangan EKUIN (dan kalangan ahli dan pemegang kebijakan pembangunan pertanian) dinilai kurang paham terhadap pentingnya sektor pertanian dalam menopang perekonomian nasional, juga dinilai kurang paham tentang pentingnya peran kelembagaan dalam pengembangan perekonomian pedesaan. Jika sejak awal kelembagaan perekonomian pedesaan dibangun secara mantap dan kekayaan alam pertanian dijadikan basis pengembangan perekonomian nasional, maka bukan saja masyarakat pedesaan akan terbebas dari krisis ekonomi yang gawat (seperti yang terjadi hingga saat ini), melainkan juga perekonomian nasional kita akan dapat mengambarkan kehebatan transformasi perekonomian masyarakat pedesaan yang dihiasi tatanan sosial yang patut dicontoh masyarakat di banyak negara. Kerapuhan kelembagaan perekonomian pedesaan ditunjukkan oleh tidak efektifnya pemberdayaan faktor kepemimpinan (sebagai penggerak kemajuan) di pedesaan, tidak terbangunnya tata nilai yang menggerakkan kemajuan ekonomi (pertanian di) pedesaan, struktur dan keorganisasian ekonomi pedesaan yang dibiarkan rapuh, otonomi yang tidak mengangkat kedaulatan (politik) masyarakat pedesaan dalam kegiatan ekonomi serta dibiarkannya faktor kompetensi sumberdaya manusia pedesaan terbengkalai.